PERAN MEDIA MASSA DALAM POLITIK LUAR NEGERI: KASUS DI INDONESIA - Asep , Setiawan (Mandala: Jurnal Ilmu Hubungan Internasional, 2019)
As a country embraces democratic values in its political system, mass media has an increasing role in influencing government policy making including foreign policy making. Study on mass media relations with foreign policy making has developed to level conceptual even theoretical framework in mass communication study. This article shows that theoretical and analytical approaches toward media and foreign policy decision making have at least seven analytical frameworks. Those tools of analysis are CNN Effect, the Indexing Hypothesis, Media – Policy Interaction Model, Positioning Theory Agenda – Setting Theory, Propaganda Model dan Manufacturing Consent. In Indonesia, study on relations between media and foreign policy has not been developed. But there is prominent case in foreign policy change of Indonesia regarding Iranian nuclear issue in United Nations Security Council.